Implementation Of Fulfillment Of Children's Rights And Protection At The Child-Friendly School Of Sd Muhammadiyah 1 Ngawi - Shofiana Eka Aulia; Muchamad Iksan; Kuswardani Kuswardani (Jurnal Indonesia Sosial Teknologi, 2023)
The purpose of writing is to find out what the implementation of the fulfillment of the right to justice and protection in SD Muhammadiyah 1 ngawi is like. This research uses a case study approach with the type of empirical juridical legal research. The school is a place for the implementation of the right to education of Indonesian citizens. The right to education is a constitutional mandate, and schools are also part of fulfilling children's rights based on Law Number 39 of 1999 concerning Human Rights and Law Number 23 of 2002 concerning Child Protection. Even so, cases of violence in the educational environment still occur frequently and tarnish the image of the world of education. Discrimination, bullying, and lack of protection for students are the main causes. The application of the right to justice and protection in schools can work well if all parties concerned are aware of the importance of these rights, especially in elementary schools. The child-friendly School Program involves 12 ministries, institutions, and foundations related to child welfare. The aim is to fulfill, guarantee, and protect children's rights, develop their interests, talents, and abilities, and prepare them to become an emotionally and spiritually intelligent generation